2020
DOI: 10.5326/jaaha-ms-6851
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy for Osteoarthritis Treatment in Dogs at Missouri Veterinary Practice

Abstract: A qualitative survey was electronically distributed to practicing veterinarians in the state of Missouri to evaluate the frequency of use and economic impact of low-level laser therapy (LLLT) for the treatment of osteoarthritis (OA) in dogs in Missouri. The survey response rate was 10% (89/867). Approximately half (43%) of respondents had LLLT units, of which all used LLLT for OA treatment in dogs. In respondents without LLLT units, 20% referred patients for LLLT OA treatment. Training was most often obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Unfortunately, a universally accepted standard for response rates has not been determined 24 . In this study the response rate from board‐certified veterinary anesthesiologists was 28% and is within the range of previously published veterinary studies 25–27 . Another limitation is that statistical testing was complicated by a low number of responses in some categories necessitating the use of the Fisher's exact test.…”
Section: Discussionmentioning
confidence: 69%
“…Unfortunately, a universally accepted standard for response rates has not been determined 24 . In this study the response rate from board‐certified veterinary anesthesiologists was 28% and is within the range of previously published veterinary studies 25–27 . Another limitation is that statistical testing was complicated by a low number of responses in some categories necessitating the use of the Fisher's exact test.…”
Section: Discussionmentioning
confidence: 69%
“…In veterinary medicine, the economic impact of OA has been calculated for an equine population [ 184 ] but has not been established for dogs yet [ 121 ], except for estimations by the veterinary health industry and insurances. Studies on the cost for physiotherapeutic measures spent for osteoarthritic dogs are missing, except for LLLT in a Midwestern state in the United States [ 121 ]. To the authors’ knowledge, there is a complete lack of studies evaluating cost efficacy of PT measures for osteoarthritis in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The term LLLT refers to a painless non-invasive therapeutic modality, operating with near-infrared or infrared-light. In North America, LLLT is extremely popular for the therapy of canine OA and OA-related musculoskeletal disorders in veterinary practice [ 121 , 122 ]. The annual economic impact of laser therapy for treatment of a single OA joint in dogs has been estimated to be approximately $6.2 million per year for one single Midwestern U.S. state [ 121 ].…”
Section: Efficacy Of Modalities Applicable By Physiotherapistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst low‐level laser therapy (LLLT) is widely used in humans with no clinically relevant reported adverse effects, only a few studies reported the use of laser for analgesic purposes in dogs (Huang et al., 2015 ; Wyszyńska & Bal‐Bocheńska, 2018 ; Youssef et al., 2016 ). The results of a recent survey study limited to the veterinarians in the state of Missouri suggest that LLLT is widely used for the treatment of canine OA, although treatment protocols were reportedly unknown and rather chosen by predetermined settings on the LLLT unit (Barger et al., 2020 ). One clinical trial conducted in 12 dogs investigated the effects of LLLT on bone healing and pain after stifle surgery, and to the best of the authors’ knowledge only three published studies reported the use of laser to treat OA‐associated chronic pain in dogs with naturally occurring OA, with promising results in terms of improved analgesia and lack of side effects (Barale et al., 2020 ; De Oliveira Reusing et al., 2021 ; Kennedy et al., 2018 ; Looney et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%